UPAYA MENINGKATKAN HASIL BELAJAR SENAM LANTAI ROL DEPAN DENGAN MENGGUNAKAN METODE DEMONSTRASI PADA KELAS IX SMPN 1 SUKODONO - Ilmiyah, Nurul; Budiarto, Fajar Teguh; Muhammad, Muhammad; Nursiyati, Nursiyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research explores the effectiveness of various teaching methods used by sports educators to instruct gymnastic agility, with the demonstration method being recognized as particularly impactful by some experts. The primary objective of this study is to investigate the implementation of the demonstration method to enhance students' learning outcomes in executing a front handspring in gymnastics, focusing on the domain of Physical and Health Education, To improve study result.The research employs a Classroom Action Research (CAR). approach and involves 36 nine-grade students from SMPN 1 Sukodono during the academic year 2023/2024 as the research subjects. To gather data, the study employs observation sheets and practical evaluation tools. Data analysis is performed using descriptive quantitative statistics. This study using 2 cycle, with each cycle consists of planning the 1)planning; 2)implementation; 3)observation; 4) reflexition. The research includes 3 which is Psychomotor affective and cognitive. An examination of the learning process for research activities going and make the survey questionnaire in the form of interest and motivation of the survey, To understand the extent of satisfaction and interest students in following the game by using the method. To understand the extent of satisfaction and interest students in following the game by using the method. The research suggests that the gymnastics floor rollers future through demontrasi method in nine-grade students from SMPN 1 Sukodono Had a positive impact. This is seen in the finality of the student study over a predetermined kkm, which is 85 is going to have an increase in the cycle of i passing students up to 42 % while the period of study is 94 % with 95 % on the motivational socket and 95.08 % on the point of interest.